2002
DOI: 10.1208/ps040422
|View full text |Cite
|
Sign up to set email alerts
|

Population analysis of the pharmacokinetics and pharmacodynamics of RWJ-270201 (BCX-1812) in treating experimental influenza A and B virus in healthy volunteers

Abstract: A PK/PD model was well utilized to characterize the effect of RWJ-270201 (BCX-1812) on the influenza A and B virus. The results from this model showed that both the loading dose and the standard dose regimens are efficacious against A and B virus. RWJ-270201 (BCX-1812) is under clinical development for the treatment of influenza A and B infections in adult and high-risk populations. It is a potent and selective inhibitor of both influenza A and B virus neuraminidases and inhibits the viral cleavage of sialic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 10 publications
(6 reference statements)
0
8
0
Order By: Relevance
“…Results from both observed and pharmacokinetic-pharmacodynamic models in healthy volunteers inoculated with influenza A or B and treated with peramivir showed that patients with greater drug exposure had a greater decline in viral titers compared with those given placebo. 8 However, the optimal pharmacokinetic parameters for peramivir efficacy in humans have not been defined. 2…”
Section: Discussionmentioning
confidence: 99%
“…Results from both observed and pharmacokinetic-pharmacodynamic models in healthy volunteers inoculated with influenza A or B and treated with peramivir showed that patients with greater drug exposure had a greater decline in viral titers compared with those given placebo. 8 However, the optimal pharmacokinetic parameters for peramivir efficacy in humans have not been defined. 2…”
Section: Discussionmentioning
confidence: 99%
“…Tissue distribution of oral and IV peramivir has not been reported. A population analysis of the pharmacokinetics of oral peramivir in treating experimental influenza A and B virus in healthy volunteers resulted in a 2‐compartmental model with first‐order absorption and elimination and volume of distribution of the central compartment (V C /F) and volume of distribution of the peripheral compartment (V P /F) of 860 and 4500 L, respectively . Weight was found to be the only significant covariate for estimated CL/F and V C /F.…”
Section: Peramivirmentioning
confidence: 99%
“…Weight was found to be the only significant covariate for estimated CL/F and V C /F. The pharmacokinetic properties were not influenced by viral type (A or B) . A population pharmacodynamic analysis showed a relationship between reduction in viral titers and increase in drug exposure …”
Section: Peramivirmentioning
confidence: 99%
See 1 more Smart Citation
“…(4B) and (4D)) [34]. BCX-1812 showed good oral bioavailability and efficacy in animal models of influenza virus infection, as well as in early clinical studies in experimentally infected subjects [36,37].…”
Section: Bcx-1812 (Rwj-270201; Peramivir)mentioning
confidence: 99%